BUILDING THE ECOLOGICAL RULE OF LAW: KNOWLEDGE, INNOVATION, AND SOCIAL ACTION (CIPEEX, 2026)
This study analyzes planned obsolescence as a phenomenon antithetical to the Ecological Rule of Law, a legal-constitutional paradigm understood as the necessary evolutionary stage of the Brazilian State to face the systemic environmental crisis. The central thesis is that ecological protection, based on Article 225 in conjunction with Article 1, III, of the Federal Constitution, is not a sectoral policy, but a structuring element that conditions the entire legal order. The justification for this approach lies in the urgency of consolidating a robust theoretical and legal framework capable of providing effective responses to the environmental degradation planned by the market. The problem focuses on demonstrating how the logic of disposable consumption collides head-on with the pillars of the Ecological State, notably intergenerational solidarity, the fundamental duty of protection, and the socio-environmental function of economic activity. The methodology starts from a conceptual analysis of the Ecological State and its foundations, applying them critically to the practice of obsolescence. It also uses a documentary analysis of case law, with special emphasis on Incident of Assumption of Jurisdiction (IAC) 13 of the STJ, as evidence of the progressive densification and concretization of this new paradigm by the Judiciary.
Keywords: estado ecológico de direito; obsolescência programada; consumismo